2021
DOI: 10.1016/j.molliq.2021.117284
|View full text |Cite
|
Sign up to set email alerts
|

Structural deformability induced in proteins of potential interest associated with COVID-19 by binding of homologues present in ivermectin: Comparative study based in elastic networks models

Abstract: The COVID-19 pandemic has accelerated the study of the potential of multi-target drugs (MTDs). The mixture of homologues called ivermectin (avermectin-B1a + avermectin-B1b) has been shown to be a MTD with potential antiviral activity against SARS-CoV-2 in vitro . However, there are few reports on the effect of each homologue on the flexibility and stiffness of proteins associated with COVID-19, described as ivermectin targets. We observed that each homologue was stably bound to identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Node interconnectivity is finally used to highlight cluster-forming nodes. For details, see refs , .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Node interconnectivity is finally used to highlight cluster-forming nodes. For details, see refs , .…”
Section: Methodsmentioning
confidence: 99%
“…molecular. For further details, see refs , . Highly cooperative and low-frequency global/essential modes in proteins represent a key aspect of the functional dynamics of proteins and are the basis for the diffusion of methods such as the NMA to be able to infer this type of collective modes.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structure of the main protease of SARS-CoV-2 (PDB: 6LU7) was used as it is a key enzyme of coronaviruses and has a fundamental role in mediating viral replication and translation, making it an attractive target for drugs ( González-Paz et al, 2021 , González-Paz et al, 2021 ). All structures were obtained in PDB format from the RCSB Protein Data Bank ( https://www.rcsb.org/ ).…”
Section: Methodological Detailsmentioning
confidence: 99%
“…The partial molar volume of protein by definition ( Awoonor-Williams and Abu-Saleh, 2021 , Azam et al, 2021 , Fornés, 2008 , González-Paz et al, 2022 , Jofily et al, 2021 ) is considered to be constituted of two volumetric contributions, a molecular or geometric contribution (volume of van der Waals and volume of internal voids ) and a non-intrinsic contribution (volumetric contribution from repulsive and attractive interactions ): is the van der Waals volumes of all the protein constitutive atoms of protein and is volume of cavities within the protein from imperfect atomic packing, dependent of temperature, proportional to molar mass , and equal to the geometric volume of protein impenetrable to surrounding solvent molecules ( Azam et al, 2021 , Azam et al, 2020 , Ball, 2017 , Barletta and Fernández-Alberti, 2018 , Barletta et al, 2019 , Brovchenko et al, 2010 , Fleming and Fleming, 2018 , González-Paz et al, 2021 ). While the thermal volume (by definition is a quantity positive, i,e, 0 ) is the empty volume around of protein which is due to the mutual protein-solvent vibrations, intermolec...…”
Section: Theorymentioning
confidence: 99%
“…More recently, Gonzalez-Paz and colleagues evaluated for the first time the effectiveness of each homolog comprising IVM. With an elastic networks model and computational and biophysical approaches, the authors observed that 22,23-dihydroavermectin B1a exhibits high affinity for the IMPα and IMPβ subunits ( Figure 2 ), while 22,23-dihydroavermectin B1b presents higher affinity for viral structures [ 216 , 217 ], especially with the SARS-CoV-2 RBD domain, further speculating that it might block the ACE2-RBD binding [ 206 ].…”
Section: Anthelmintic Drugs Against Sars-cov-2mentioning
confidence: 99%